2012
DOI: 10.1016/j.mayocp.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis Among Somali Immigrants in Minnesota: Association of Hepatitis C With Hepatocellular Carcinoma

Abstract: Objective To study the frequencies of chronic viral hepatitis B (HBV), hepatitis C (HCV), and their associations with hepatocellular carcinoma (HCC) in immigrant Somalis seen at Mayo Clinic, Rochester, Minnesota. Methods We investigated the frequencies of HBV and HCV infection and HCC in immigrant Somalis seen at Mayo Clinic, Rochester, Minnesota between July 1, 1996 and October 31, 2009. Non-Somali Olmsted County residents served as controls. Results For Somali males and females, age-adjusted proportions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Shire et al [24] studied a sample of Somali immigrants to Minnesota who had HCC. They found that both HBV and HCV occurred frequently in this sample of immigrants; however, HCV was the major risk factor for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Shire et al [24] studied a sample of Somali immigrants to Minnesota who had HCC. They found that both HBV and HCV occurred frequently in this sample of immigrants; however, HCV was the major risk factor for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a survey of over 4300 Asian immigrants to New York City showed that 13% of this cohort was HBsAg positive [34]. Similarly, a study of Somali immigrants in Minnesota showed HBV prevalence rates of ten times the baseline population [35]. Given these data, the true prevalence of HBV in the US has been estimated to be as high as 2.2 million individuals, with up to 1.3 million foreign-born HBV positive individuals [36].…”
Section: Prevalence Of Viral Hepatitis Among Migrantsmentioning
confidence: 99%
“…By design it omits several large populations of persons at increased risk of HCV infection, including homeless persons, those in jail or prison, and those living on Indian reservations. Second, several additional groups at increased risk of hepatitis C, while not excluded from the NHANES sampling frame, are poorly represented because of small sample sizes, including Puerto Rican Americans, other ethnic minorities, and people born in high‐prevalence countries . Third, nonresponse bias could result in underestimation if persons at elevated risk of hepatitis C differentially opt not to participate or do not provide a blood specimen.…”
mentioning
confidence: 99%